Targeting the MICA/B-NKG2D axis in cancer: from molecular structure to immunotherapeutic strategies—a narrative review - Zheng, Yuwei; Ding, Wanyi; Chen, Bingbing; Geng, Caizheng; Li, Xiaowei (Translational Cancer Research, 2026)
The interaction between major histocompatibility complex class I chain-related proteins A and B (MICA/B) and the activating receptor natural killer group 2 member D (NKG2D) represents a critical axis in anti-tumor immunity. This pathway plays a central role in the recognition and elimination of stressed or transformed cells by natural killer (NK) cells and CD8+ T cells. However, tumors frequently develop diverse mechanisms to disrupt this axis, leading to immune escape. This review aims to provide a comprehensive overview of the molecular structure, regulatory mechanisms, and therapeutic targeting strategies of the MICA/B-NKG2D pathway in cancer.